2016
DOI: 10.1038/cddis.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

The oncolytic peptide LTX-315 triggers immunogenic cell death

Abstract: LTX-315 is a cationic amphilytic peptide that preferentially permeabilizes mitochondrial membranes, thereby causing partially BAX/BAK1-regulated, caspase-independent necrosis. Based on the observation that intratumorally injected LTX-315 stimulates a strong T lymphocyte-mediated anticancer immune response, we investigated whether LTX-315 may elicit the hallmarks of immunogenic cell death (ICD), namely (i) exposure of calreticulin on the plasma membrane surface, (ii) release of ATP into the extracellular space,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 38 publications
0
88
0
Order By: Relevance
“…In cultured 4T1 mouse breast cancer cells, we observed changes indicative of ICD after SGT-53 treatment including increased surface expression of the ER protein CRT and release of cell death associated molecular patterns (HMGB1 and ATP). 34 Several additional alterations in immunogenicity were also observed with SGT-53 treatment including type I IFN responses and increased tumor expression of CD80, CD86, FAS, TAP1/2, and MHC I molecules in vivo . We have previously shown that SGT-53 treatment of MOC1 head and neck cancer cells could upregulate the expression of genes involved in antigen processing and presentation including CRT, calnexin, endoplasmic reticulum amino peptidase 1, and TAP1/2 involving stimulator of interferon genes (STING) pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In cultured 4T1 mouse breast cancer cells, we observed changes indicative of ICD after SGT-53 treatment including increased surface expression of the ER protein CRT and release of cell death associated molecular patterns (HMGB1 and ATP). 34 Several additional alterations in immunogenicity were also observed with SGT-53 treatment including type I IFN responses and increased tumor expression of CD80, CD86, FAS, TAP1/2, and MHC I molecules in vivo . We have previously shown that SGT-53 treatment of MOC1 head and neck cancer cells could upregulate the expression of genes involved in antigen processing and presentation including CRT, calnexin, endoplasmic reticulum amino peptidase 1, and TAP1/2 involving stimulator of interferon genes (STING) pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Downstream of mitochondria, then a variety of lethal signaling events (that can be partially inhibited by a combination of caspase inhibition by Z-VAD-fmk and RIP1 inhibition by necrostatin) come into action, as this is often observed, 23 in line with the increasing awareness that the clear-cut distinction between apoptotic and necroptotic degradation events is a didactic oversimplification. 24 Similar to LTX-315, 5 LTX-401 triggers all biochemical hallmarks of ICD including ATP release, calreticulin exposure, nuclear HMGB1 exodus and the induction of a type-1 interferon response. These findings, which have been obtained in vitro, suggest that LTX-401 can stimulate the full spectrum of events required for (ATP-dependent) attraction of DC precursors into the tumor bed, the (calreticulin-dependent) transfer of tumor antigens from cancer cells to DC precursors, the (HMGB1-dependent) maturation of DC for optimal antigen presentation of tumor-associated antigens, and (the type-1 interferon-dependent) recruitment of T cells into the tumor bed.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 LTX-315 is being developed for the local treatment of superficial human cancers based on the observations that it causes potent cytotoxic effects and that it might stimulate a local immune response that may prolong its antineoplastic action over time. [5][6][7] This latter property makes LTX-315 an interesting lead compound, especially in view of its capacity to reverse the resistance of cancers to immune checkpoint blockade with anti-CTLA4 antibodies in preclinical models. 6 LTX-315 has the capacity of causing a necrotic cell death (i.e., cell death without caspase activation and without morphological features of apoptosis such as nuclear fragmentation) that is partially relying on mitochondrial membrane permeabilization by this oncolytic peptide, 4 which actually redistributes specifically towards the mitochondrial compartment.…”
mentioning
confidence: 99%
See 2 more Smart Citations